The Influence of Management Information Systems on Employee Performance through Decision Making Effectiveness at PT Indah Kiat Pulp & Paper Tbk Perawang - Mujabah, Ibnatul; Sihombing, Siska Priscila Br; Siregar, Rina Pebriani; Febrina, Sulistika; Sumitro, Sumitro (Journal of Economics and Social Sciences (JESS), 2026)
Background: The increasing adoption of digital systems in industrial organizations requires effective Management Information Systems (MIS) to support accurate and timely decision making processes. However, the mechanism through which MIS influences employee performance remains underexplored, particularly through decision-making effectiveness. Objective: This study aims to examine the effect of MIS on employee performance through decision-making effectiveness as a mediating variable. Method: This study employed a quantitative approach using a survey method involving 117 employees at PT Indah Kiat Pulp & Paper Tbk. Data were collected using structured questionnaires with a five point Likert scale and analyzed using Structural Equation Modeling Partial Least Squares (SEM PLS). Results: The findings indicate that MIS has a significant positive effect on decision-making effectiveness and employee performance. Decision-making effectiveness also significantly influences employee performance and acts as a mediating variable in the relationship between MIS and performance. Conclusion: MIS enhances employee performance both directly and indirectly by improving decision-making effectiveness. The results highlight the importance of developing integrated and user-friendly information systems to support data-driven decision-making in organizations.